1982
DOI: 10.1093/nar/10.22.7075
|View full text |Cite
|
Sign up to set email alerts
|

A general strategy for cloning double-stranded RNA: nucleotide sepuence of the Simian-11 rotavirus gene 8

Abstract: Using Simian-11 rotavirus RNA, a strategy has been developed for the production of full length cloned copies of the genes of double-stranded (dsRNA) viruses. Genomic RNA segments were polyadenylated and reverse transcribed to yield a mixture of full length cDNA copies of both possible polarities. The cDNAs were annealed, filled in to complete any partial copies, tailed and inserted into the PstI site of pBR322 using dG/dC tailing. Cloned rotavirus cDNA gene copies were assigned to genomic RNA segments by North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
49
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…Priess et al (1980) found a linear relationship between length and number of bp of dsDNA in the range of 400 to 10000 bp and there is no reason that this should not be the case for the size range of dsRNAs investigated (Vasquez & Kleinschmidt, 1968). Our measurements agree, with a difference of ~< 6~ (Table 1, column 8), with the cDNA size estimates of size classes II (segments 5 and 6), III (segments 7 to 9) and IV (segments 10 and 11) (Both et al, 1982), whereas they are 8 to 17 ~ lower for molecules of size class I (segments 1 to 4). Segments 1, 2 and 3 of SA11 virus from which the values of Both et al (1982) are obtained and the corresponding segments of the UK bovine rotavirus migrate very similarly (Pereira et al, 1983) whereas segment 4 of the UK bovine rotavirus migrates slightly more slowly, i.e.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…Priess et al (1980) found a linear relationship between length and number of bp of dsDNA in the range of 400 to 10000 bp and there is no reason that this should not be the case for the size range of dsRNAs investigated (Vasquez & Kleinschmidt, 1968). Our measurements agree, with a difference of ~< 6~ (Table 1, column 8), with the cDNA size estimates of size classes II (segments 5 and 6), III (segments 7 to 9) and IV (segments 10 and 11) (Both et al, 1982), whereas they are 8 to 17 ~ lower for molecules of size class I (segments 1 to 4). Segments 1, 2 and 3 of SA11 virus from which the values of Both et al (1982) are obtained and the corresponding segments of the UK bovine rotavirus migrate very similarly (Pereira et al, 1983) whereas segment 4 of the UK bovine rotavirus migrates slightly more slowly, i.e.…”
supporting
confidence: 70%
“…(1978), applying Shatkin's approach to rotavirus RNAs, obtained estimates (Table 1, column 3) which for RNA segments 7 11 were closer to their real size than the estimates obtained by Newman et al (1975), Verly & Cohen (1977), Todd etal. (1980 and Rodger & Holmes cited by Both et al (1982) (Table 1, columns 1, 2, 4 and 5 respectively). However, the size estimates of the large dsRNA segments of rotavirus by Kalica et al (1978) were considerably smaller than the corresponding values of most other estimates• Since 1982, procedures have been published which have allowed cloning of the rotavirus genome (McCrae & McCorquodale, 1982;Both et al, 1982Both et al, , 1983Imai et al, 1983;Dyall-Smith et al, 1983).…”
mentioning
confidence: 94%
See 3 more Smart Citations